Performance of indigenous chicken under intensive rearing with various litter materials - M. Sulistyoningsih; Dwi Sunarti; Ejeng Suprijatna; I. Isroli (International Journal of Science and Engineering, 2013)
The purpose of the research was to  obtain  information regarding the performance of indigenous chicken  under   intensive  rearing. The  performance criteria were the increasing body abdominal weight, fat, rectal temperature, and the indigenous chicken’s mortality within the 5-week starter phase treatment. Research was conducted using 108 Day Old Chick (DOC). Data variance was analysed  based  on  the  split  plot  design  (3  types  of cage  litter  materials,  5 weeks  of data collection,  and   4   replications)   for   weight   gain   and   abdominal   fat parameters,   and completely  randomized  design  in  time  for rectal temperature. The result indicated a significant  effect  of  different  litter  materials  towards  weight  gain  (P  <0.01), the  highest body weight  was found on  chicken treated with rice straw litter; there was  no effect  of litter material on abdominal fat percentage; there was a significant effect (P < 0.01) of age towards rectal temperature; and there were no  interactions  between litter material with age,  on body weight  gain,  abdominal  fat,  and  rectal  temperature.  Chickens  under intensive  rearing  in rice straw floored cages were proven to have a mortality rate reduced by 3.7% in the starter phase.doi: http://dx.doi.org/10.12777/ijse.4.2.2013.52-56 [How to cite this article: Sulistyoningsih, M., Sunarti, D., Suprijatna, E., & Isroli, I. (2013). Performance of indigenous chicken under intensive rearing with various litter materials. INTERNATIONAL JOURNAL OF SCIENCE AND ENGINEERING, 4(2), 52-56; doi: http://dx.doi.org/10.12777/ijse.4.2.2013.52-56